THE EFFECT OF KUFNER INTERFACING ON THE COLLAR OUTCOME OF MEN'S SUIT ON SIZE M DUMMY - Riska Savitri; Weni Nelmira (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research is motivated by the need to understand the impact of Kufner interfacing on the collar results of men's blazers on size M dummies. The purpose of this study is to describe the results of the blazer collar based on three main aspects: flatness, neatness, and balance, using Kufner interfacing. This study used an experimental method conducted from November to February 2024. Primary data were obtained from the assessments of 16 panelists, consisting of 4 lecturers and 12 trained students. The research instrument was a questionnaire, and the data were analyzed using descriptive analysis and the Friedman test to test the hypothesis. The results showed that the use of Kufner interfacing resulted in flatness of 80.47%, neatness of 91.67%, and balance of 88.28%, with all aspects rated in the “Very Good” category. The hypothesis test showed that Kufner interfacing significantly affected the flatness, neatness, and balance of the blazer collar, with a probability value smaller than the significance level (p < 0.05). This indicates that Kufner interfacing provides optimal results in the process of making men's blazer collars on size M dummies.